Evaluation of the Anti-Toxoplasma gondii Efficacy, Cytotoxicity, and GC/MS Profile of Pleopeltis crassinervata Active Subfractions - Jhony Anacleto-Santos; Fernando Calzada; Perla Yolanda López-Camacho; Teresa de Jesús López-Pérez; Elba Carrasco-Ramírez; Brenda Casarrubias-Tabarez; Teresa I. Fortoul; Marcela Rojas-Lemus; Nelly López-Valdés; Norma Rivera-Fernández (MDPI AG, 2023)
Pleopeltis crassinervata (Pc) is a fern that, according to ethnobotanical records, is used in Mexican traditional medicine to treat gastrointestinal ailments. Recent reports indicate that the hexane fraction (Hf) obtained from Pc methanolic frond extract affects Toxoplasma gondii tachyzoite viability in vitro; therefore, in the present study, the activity of different Pc hexane subfractions (Hsf) obtained by chromatographic methods was evaluated in the same biological model. Gas chromatography/mass spectrometry (GC/MS) analysis was carried out for hexane subfraction number one (Hsf1), as it showed the highest anti-Toxoplasma activity with a half-maximal inhibitory concentration (IC50) of 23.6 µg/mL, a 50% cytotoxic concentration (CC50) of 398.7 µg/mL in Vero cells, and a selective index (SI) of 16.89. Eighteen compounds were identified by Hsf1 GC/MS analysis, with the majority being fatty acids and terpenes. Hexadecanoic acid, methyl ester was the most commonly found compound (18.05%) followed by olean-13(18)-ene, 2,2,4a,8a,9,12b,14a-octamethyl-1,2,3,4,4a,5,6,6a,6b,7,8,8a,9,12,12a,12b,13,14,14a,14b-eicosahydropicene, and 8-octadecenoid acid, methyl ester, which were detected at 16.19%, 12.53%, and 12.99%, respectively. Based on the mechanisms of action reported for these molecules, Hsf1 could exert its anti-Toxoplasma activity mainly on T. gondii lipidomes and membranes.